Lipophagy maintains energy homeostasis in the kidney proximal tubule during prolonged starvation. Issue 10 (3rd October 2017) - Minami, Satoshi; Yamamoto, Takeshi; Takabatake, Yoshitsugu; Takahashi, Atsushi; Namba, Tomoko; Matsuda, Jun; Kimura, Tomonori; Kaimori, Jun-ya; Matsui, Isao; Hamano, Takayuki; Takeda, Hiroaki; Takahashi, Masatomo; et al.
ABSTRACT: Macroautophagy/autophagy is a self-degradation process that combats starvation. Lipids are the main energy source in kidney proximal tubular cells (PTCs). During starvation, PTCs increase fatty acid (FA) uptake, form intracellular lipid droplets (LDs), and hydrolyze them for use. The involvement of autophagy in lipid metabolism in the kidney remains largely unknown. Here, we investigated the autophagy-mediated regulation of renal lipid metabolism during prolonged starvation using PTC-specific Atg5 -deficient ( atg5 -TSKO) mice and an in vitro serum starvation model. Twenty-four h of starvation comparably induced LD formation in the PTCs of control and atg5 -TSKO mice; however, additional 24 h of starvation reduced the number of LDs in control mice, whereas increases were observed in atg5 -TSKO mice. Autophagic degradation of LDs (lipophagy) in PTCs was demonstrated by electron microscopic observation and biochemical analysis. In vitro pulse-chase assays demonstrated that lipophagy mobilizes FAs from LDs to mitochondria during starvation, whereas impaired LD degradation in autophagy-deficient PTCs led to decreased ATP production and subsequent cell death. In contrast to the in vitro assay, despite impaired LD degradation, kidney ATP content was preserved in 48-h starved atg5 -TSKO mice, probably due to increased utilization of ketone bodies. This compensatory mechanism was accompanied by a higher plasma FGF21 (fibroblast growth factor 21) level and its expression in the PTCs; however, this was not essential for the production of ketone bodies in the liver during prolonged starvation. In conclusion, lipophagy combats prolonged starvation in PTCs to avoid cellular energy depletion.